Weed competition in pasture of the Panicum maximum BRS Tamani (Research, Society and Development, 2021)
For the adoption of weed management strategies, it is essential to know the periods of interference between the weed community and the culture of economic interest. This research aimed to evaluate the effects of weed competition on the implantation of Panicum maximum BRS Tamani pasture and on its regrowth after cutting. Two trials were conducted in randomized blocks, with four replications. In the first trial, the forage was kept in contact with the weeds for periods of 0, 7, 14, 21, 28, 35, 42, 49, 56 and 63 days after the emergence (DAE) of the pasture, and in the second trial, the forage was kept without the weeds living together for the same periods until the forage cut, at 63 DAE. The plots were kept free of weeds by manual weeding, according to treatment. Weed competition was established soon after the forage emergence and reduced the forage yield. The critical period for preventing weed interference in P. maximum BRS Tamani pasture was between 1 (one) and extended up to 42 DAE. Weed interference decreased the production of forage, as well as the percentage of vegetation cover, canopy height and forage tillering.